Forma urbana y movilidad sustentable: reflexiones sobre Montevideo. - Vincent, Valentina (Universidad ORT Uruguay, 2018)
The following article reflects on the relationship between the built environment and mobility. Sustainable mobility, which prioritizes public transit and actives modes, has a starring role in the future of urban planning. In the literature, this relationship between urban form and mobility has been vastly studied. Several authors have established which variables of urban form affect mobility, and what can be done through design to foster sustainable mobility. Also, the relevance of attitudinal factors has been studied and how, if possible, citizens’ behavior could be affected in order to promote sustainable attitudes. Through the case of Montevideo, the relation between urban form and mobility will be exemplified. Also, the objectives and strategies of the city government’s plans will be analyzed and conclusions will be made according to the cited literature